2017
DOI: 10.1051/0004-6361/201628960
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking the Multidimensional Stellar Implicit Code MUSIC

Abstract: We present the results of a numerical benchmark study for the MUltidimensional Stellar Implicit Code (MUSIC) based on widely applicable two-and three-dimensional compressible hydrodynamics problems relevant to stellar interiors. MUSIC is an implicit large eddy simulation code that uses implicit time integration, implemented as a Jacobian-free Newton Krylov method. A physics based preconditioning technique which can be adjusted to target varying physics is used to improve the performance of the solver. The prob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 56 publications
0
30
0
Order By: Relevance
“…In our implementation (adapted from original routines for the Music code; Goffrey et al 2017), we compute the pressure and other required EOS variables for a particular composition by interpolation between sets of tables for different hydrogen abundance X = 0.0, 0.2, 0.4, 0.6, 0.8 and metallicity Z = 0.0, 0.02, 0.04. Pressure is calculated with bicubic interpolation, and Γ 1 ≡ ∂ln P /∂lnρ| s with bilinear interpolation, in log u and log V ≡ logρ − 0.7log u + 20.…”
Section: Methodsmentioning
confidence: 99%
“…In our implementation (adapted from original routines for the Music code; Goffrey et al 2017), we compute the pressure and other required EOS variables for a particular composition by interpolation between sets of tables for different hydrogen abundance X = 0.0, 0.2, 0.4, 0.6, 0.8 and metallicity Z = 0.0, 0.02, 0.04. Pressure is calculated with bicubic interpolation, and Γ 1 ≡ ∂ln P /∂lnρ| s with bilinear interpolation, in log u and log V ≡ logρ − 0.7log u + 20.…”
Section: Methodsmentioning
confidence: 99%
“…The code has been benchmarked against a number of standard hydrodynamical test problems (e.g. Goffrey et al 2017) and has been applied to a number of stellar physics problems, including accretion (Geroux et al 2016) and convective overshooting (Pratt et al 2017, Pratt, J. et al 2020.…”
Section: Musicmentioning
confidence: 99%
“…This is for example employed by the MUSIC code in combination with a staggered spatial grid. Benchmark tests have shown that the code is able to evolve flows at Mach numbers down to Ma ≈ 10 −6 (Viallet et al 2016) and that a hydrostatic atmosphere remains stable (Goffrey et al 2017).…”
Section: Introductionmentioning
confidence: 99%